Late Ediacaran occurrences of the organic-walled microfossils Granomarginata and flask-shaped Lagoenaforma collaris gen. et sp. nov. - Agić, Heda; Högström, Anette; Jensen, Sören; Ebbestad, Jan Ove R.; Vickers-Rich, Patricia; Hall, Michael; Matthews, Jack J.; Meinhold, Guido; Høyberget, Magne; Taylor, Wendy L. (Geological Magazine, 2021)
New occurrences of flask-shaped and envelope-bearing microfossils, including the predominantly Cambrian taxon Granomarginata, are reported from new localities, as well as from earlier in time (Ediacaran) than previously known. The stratigraphic range of Granomarginata extends into the Cambrian System, where it had a cosmopolitan distribution. This newly reported Ediacaran record includes areas from Norway (Baltica), Newfoundland (Avalonia) and Namibia (adjacent to the Kalahari Craton), and puts the oldest global occurrence of Granomarginata in the Indreelva Member (< 563 Ma) of the Stáhpogieddi Formation on the Digermulen Peninsula, Arctic Norway. Although Granomarginata is rare within the assemblage, these new occurrences together with previously reported occurrences from India and Poland, suggest a potentially widespread palaeogeographic distribution of Granomarginata through the middle–late Ediacaran interval. A new flask-shaped microfossil Lagoenaforma collaris gen. et sp. nov. is also reported in horizons containing Granomarginata from the Stáhpogieddi Formation in Norway and the Dabis Formation in Namibia, and flask-shaped fossils are also found in the Gibbett Hill Formation in Newfoundland. The Granomarginata–Lagoenaforma association, in addition to a low-diversity organic-walled microfossil assemblage, occurs in the strata postdating the Shuram carbon isotope excursion, and may eventually be of use in terminal Ediacaran biostratigraphy. These older occurrences of Granomarginata add to a growing record of body fossil taxa spanning the Ediacaran–Cambrian boundary.